The Final Frontier: The Integration of Banking and Commerce. Part 2: Risk and Return Using Efficient Portfolio Analysis - Alan K. Reichert; Larry D. Wall; Hsin-yu Liang (Economic Review, 2008)
In the first part (in the previous issue of Economic Review) of this two-part study, the authors identified a number of possible benefits from combining banking and commerce, including portfolio diversification, the creation of internal capital markets, and economies of scale and scope. This second part of the study analyzes the one source of possible gainsportfolio diversificationthat can be estimated with existing data. Using methodologies from previous studies, the authors combine ten financial and nonfinancial industries into hypothetical portfolios using industry-level profitability data calculated from corporate tax returns filed with the Internal Revenue Service between 1994 and 2004. The analysis demonstrates that pairwise combinations of banks with construction firms or with retail firms would have produced substantially higher returns on equity with less risk during the sample period. Efficient portfolios combining banks with several other industries showed even higher levels of returns relative to risk, although banks were not necessarily a dominant part of some combinations. These findings suggest that portfolio diversification could be an important benefit from combining banks with some types of nonbank firms. The authors stress that bank management contemplating diversification into the commercial sector must be selective about which specific industries they choose, while corporate management interested in moving into banking might need to settle for somewhat lower returns to achieve a substantial reduction in risk.
Keywords: G21; G34; G28; 330; banking and commerce; portfolio diversification; Bank; Handel; Bankrecht; Deregulierung; Diversifikation; Rentabilität; USA